2021
DOI: 10.1007/s10909-021-02577-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Topological Defect on the Energy Spectra and Thermo-magnetic Properties of $$CO$$ Diatomic Molecule

Abstract: Confinement effects of Aharonov-Bohm (AB) flux and magnetic fields with topological defect on CO diatomic molecule modeled by screened modified Kratzer potential is investigated in this paper. The all-encompassing effects of the fields and topological defect result in a strongly repulsive system. We discover that the collective effect of the fields and defect is intense than the lone and dual effect and consequently there is a substantial shift in the bound state energy of the system. We also find that to sust… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 95 publications
(106 reference statements)
0
28
0
Order By: Relevance
“…Furthermore, for many years, the study of quantum dynamics of a single particle interacting in a given potential with a topological defect has been a subject of great interest to researchers. The formation of a topological defect is thought to have occurred during a phase transition in the early universe [17][18][19][20]. The effects of topological defects on the dynamics of both non-relativistic and relativistic quantum mechanical systems have recently piqued researchers' interest, such as screw dislocation [21], bound eigenstates of electron and holes to a declination.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, for many years, the study of quantum dynamics of a single particle interacting in a given potential with a topological defect has been a subject of great interest to researchers. The formation of a topological defect is thought to have occurred during a phase transition in the early universe [17][18][19][20]. The effects of topological defects on the dynamics of both non-relativistic and relativistic quantum mechanical systems have recently piqued researchers' interest, such as screw dislocation [21], bound eigenstates of electron and holes to a declination.…”
Section: Introductionmentioning
confidence: 99%
“…They observed that SOI has a considerable effect on the properties of the magnetopolaron and that there is an occurrence of an inflection point in the variation of the ground state binding energy as a function of SOI and temperature. The effect of the external field on thermodynamic quantities has been studied in some earlier works [57][58][59][60][61][62][63][64][65][66][67][68][69][70], and currently, now the SOI effect on thermodynamic properties in the quantum system has not been studied in depth, although the role SOI also plays an important role in the quantum properties as well as in the thermodynamic quantities of these quantum systems. Several works have been done on the effect of laser radiation on the electronic properties and thermodynamic properties; for example, Fobasso et al [71] have shown that the laser can stabilize the bipolaron and improve the quantum coherence of the system.…”
Section: Introductionmentioning
confidence: 99%
“…We hope to extend this model to include anisotropic plasma which plays an important role for analysis of quark gluon plasma as a future work. In addition, thermodynamics properties of heavy mesons in the non-relativistic quark model in the presence of AB and magnetic fields could also be considered as an extension of our study [37][38][39][40][41][42].…”
Section: -Summary and Conclusionmentioning
confidence: 99%